Physical oceanography during METEOR cruise M179/2 (CoastCarb) - Kai Schwalfenberg; Jochen Wollschläger; Bernd Krock (PANGAEA, 2023)
The data presented here were collected during the cruise M179/2 (CoastCarb) with RV Meteor from Punta Arenas (Chile) to Montevideo (Uruguay) (January, 18th, 2022 to February 20th, 2022). In total, 49 vertical CTD-hauls were conducted. The CTD system used was a Sea-Bird Electronics Inc. SBE 911plus probe (SN 09-1266). The CTD was attached to a SBE 32 Carousel Water Sampler containing 24 10-liter Ocean Test Equipment Inc. bottles. The system was equipped with double temperature (SBE 3) and conductivity sensors (SBE 4), a pressure sensor (Digiquartz) an oxygen optode (Aanderaa Optode 4831F), an altimeter (Benthos), and a combined chlorophyll fluorometer and turbidity meter (WET Labs ECO_AFL FL). The sensors were pre-calibrated by the respective manufacturers. Data were recorded with the Seasave V 7.26.7.107 software and processed using the SeaBird SBE Data Processing software. The ship position was derived from the shipboard GPS-system linked to the CTD data. The time zone is given in UTC. Raw data on request. The data was checked for quality and plausibility. Since no calibration of the sensors was performed at the end of the cruise, the quality control was performed as follows. For the parameters that were measured redundant (temperature, potential temperature, salinity, conductivity, and density) the difference to each measurement point was calculated and the respective σ2 normal distribution was calculated. All values falling within the 95% interval were marked with QF 2, and the other values were marked with QF 5. For the oxygen measurements, a manual visual inspection was performed and the values were marked accordingly. The two optical parameters fluorescence and turbidity were marked with QF 2 throughout, since natural outliers can occur here due to particles.